Can Indonesia’s Laws Keep Up? Protecting Consumer Rights in Digital Transactions - Bambang Sugeng Ariadi Subagyono; Mochamad Kevin Romadhona; Zahry Vandawati Chumaida; Bambang Suheryadi; Noureldin Samy Elkhashab (Journal of Law and Legal Reform)
This research examines dispute settlement mechanisms within the framework of Indonesia's consumer protection laws and the Electronic Information and Transaction Law (ITE Law). Utilizing a normative legal methodology, the study analyzes relevant legal principles and doctrines, particularly focusing on Law No. 8 of 1999 on Consumer Protection and the Civil Code. The key findings of the study are twofold. First, it identifies that corporate entities bear responsibility for consumer losses under both the Consumer Protection Law and the ITE Law, which provides a legal structure for resolving disputes related to electronic transactions. However, the research also reveals a critical distinction: disputes arising from online purchases generally fall under the ITE Law, rather than the Consumer Protection Law. Second, the study highlights the challenge of interpreting the term "consumer" within the Consumer Protection Law, which explicitly refers to the final beneficiary of a product or service. This definition creates ambiguity in cases involving intermediaries or non-end consumers in online transactions. The study's contribution lies in its identification of a legal gap in the current regulatory framework. It suggests that the Consumer Protection Law may require revision to better address the complexities of modern e-commerce, particularly in distinguishing between end consumers and non-end consumers. By doing so, the research provides a foundation for future legal reforms aimed at improving the protection of consumers in the digital marketplace.